2022
DOI: 10.1371/journal.pone.0269689
|View full text |Cite
|
Sign up to set email alerts
|

Total collagen content and distribution is increased in human colon during advancing age

Abstract: Background The effect of ageing on total collagen content of human colon has been poorly investigated. The aim of this study was to determine if ageing altered total collagen content and distribution in the human colon. Methods Macroscopically normal ascending colon was obtained at surgery from cancer patients (n = 31) without diagnosis of diverticular disease or inflammatory bowel disease. Masson’s trichrome and Picrosirius red stains were employed to identify the total collagen content and distribution wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…No differences in the total collagen content was observed between hog/sheep casings in all samples, even though they had different toughness. A study on total collagen content and distribution in the human colon showed similar results indicating that the percentage mean intensity of total collagen staining in the submucosa was 74 (3.2)% in the adult ascending colon [ 25 ].…”
Section: Resultsmentioning
confidence: 84%
“…No differences in the total collagen content was observed between hog/sheep casings in all samples, even though they had different toughness. A study on total collagen content and distribution in the human colon showed similar results indicating that the percentage mean intensity of total collagen staining in the submucosa was 74 (3.2)% in the adult ascending colon [ 25 ].…”
Section: Resultsmentioning
confidence: 84%
“… The sensitivity of this protocol is such that it is now applicable to quantify hydroxyproline content in FFPE samples using only a few 10µm sections. In the analysis of the amount of hydroxyproline content in colonic samples, previous studies reported no statistically significant differences in the amount of hydroxyproline content between treated (with histoclear) and untreated (with paraffin) samples [6 , 7] , indicating that this technique can be employed without the use of xylene/histoclear (see Fig. 5 ).…”
Section: Critical Parametersmentioning
confidence: 85%
“…These include those associated with tissue damage, such as inflammatory bowel disease [4] diverticular disease and anastomotic leakage after large bowel surgery [5] . In addition, the human colon, at the level of submucosa and muscularis externa, shows an increase in total collagen fibres among the elderly [6 , 7] indicating that the functions of these sublayers may be vulnerable to age-associated physiological changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most collagen and elastin of the GI organs are situated in the mucosal, submucosal and outer layers (Van de Graaff 1986 ; Baidoo et al. 2022 ; Durcan et al. 2022a ).…”
Section: Introductionmentioning
confidence: 99%